The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1016/j.jnutbio.2014.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-lipoic acid improves high-fat diet-induced hepatic steatosis by modulating the transcription factors SREBP-1, FoxO1 and Nrf2 via the SIRT1/LKB1/AMPK pathway

Abstract: Understanding the mechanism by which alpha-lipoic acid supplementation has a protective effect upon nonalcoholic fatty liver disease in vivo and in vitro may lead to targets for preventing hepatic steatosis. Male C57BL/6J mice were fed a normal diet, high-fat diet or high-fat diet supplemented with alpha-lipoic acid for 24 weeks. HepG2 cells were incubated with normal medium, palmitate or alpha-lipoic acid. The lipid-lowering effects were measured. The protein expression and distribution were analyzed by Weste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
70
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(78 citation statements)
references
References 40 publications
8
70
0
Order By: Relevance
“…Indeed, (S)YS-51 increased SIRT1 mRNA and protein expression in the livers of HFD mice. It has been shown that SIRT1 is activated by an increased NAD + /NADH ratio and then deacetylates by liver kinase B1 (LKB1) which follows phosphorylation of AMPK (Ruderman et al, 2010;Yang et al, 2014). In agreement with these reports, (S)YS-51 increased the NAD + /NADH ratio and phosphorylation of LKB1, which resulted in an increase of phosphorylation of AMPK in the livers of HFD mice in a dose of 10 mg/kg.…”
Section: Discussionsupporting
confidence: 69%
“…Indeed, (S)YS-51 increased SIRT1 mRNA and protein expression in the livers of HFD mice. It has been shown that SIRT1 is activated by an increased NAD + /NADH ratio and then deacetylates by liver kinase B1 (LKB1) which follows phosphorylation of AMPK (Ruderman et al, 2010;Yang et al, 2014). In agreement with these reports, (S)YS-51 increased the NAD + /NADH ratio and phosphorylation of LKB1, which resulted in an increase of phosphorylation of AMPK in the livers of HFD mice in a dose of 10 mg/kg.…”
Section: Discussionsupporting
confidence: 69%
“…Herein we found that tRES also induces expression of Glo1 with high E max . Our recent studies (7,8) and those of others (31) suggest that this is achieved by preventing nuclear acetylation and inactivation of Nrf2 via increasing in situ activity of sirtuin-1. At low tRES concentrations, this occurs through inhibition of cAMP phosphodiesterases, activation of AMPK, and increased NAD + .…”
Section: (232%) [-]mentioning
confidence: 81%
“…2B), which is likely due to inhibitory nuclear acetylation of Nrf2 blocking a high E max . Combination with tRES and HESP provides for faster nuclear translocation and decreased inactivation of Nrf2 (7,8,31). Use of HESP rather than related dietary glycoside hesperidin found in citrus fruits (34) is likely crucial: HESP has ;70-fold greater potency in Nrf2 activation and higher bioavailability than hesperidin (35).…”
Section: (232%) [-]mentioning
confidence: 99%
“…Kawai et al (7) demonstrated that SIRT1-mediated deacetylation of the NRF2 protein terminated the transcription of antioxidant genes in vitro. However, other studies have demonstrated that SIRT1 overexpression significantly promoted the nuclear accumulation, DNA binding and transcriptional activity of NRF2 and NRF2-mediated gene expression (8,9,23). In the current study, an increase in the SIRT1 expression levels by Res was associated with a high level of NRF2.…”
Section: Discussionmentioning
confidence: 93%